The Self-Perceived Subject-Specific Professional Competencies of Slovenian Physical Education Teachers in Different Working Environments : Samopimanje predmetnih stručnih kompetencija slovenskih učitelja tjelesne i zdravstvene kulture u različitim radnim okruženjima - Kovač, Marjeta (Array, 2021)
This cross-sectional study was designed to analyse the differences in the subject-specific competencies of Slovenian Physical Education (PE) teachers according to their physical working environment. The participants, 681 Slovenian PE teachers, evaluated their professional subject-specific competencies (n=40) on a four-level Likert scale and two factors of their physical working environment (size of sports facilities and their equipment) with a self-administered questionnaire. Differences in their self-perceptions about subject-specific competencies between those working in good conditions and those working in poorer conditions were identified with the Mann-Whitney test for independent samples, and Cliff"s delta was used to estimate the size of the differences. The results show that higher perceptions of subject-specific competencies of PE teachers are mainly affected by the equipment of sports facilities, not their size; therefore, local communities and the state should ensure that all schools have roughly equal well-equipped sports facilities.